2015
DOI: 10.1371/journal.pone.0143909
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Powder Diet After Weaning Induces Sleep, Behavioral, Neuroanatomical, and Neurophysiological Changes in Mice

Abstract: The purpose of this study is to clarify the effects of chronic powder diet feeding on sleep patterns and other physiological/anatomical changes in mice. C57BL/6 male mice were divided into two groups from weaning: a group fed with solid food (SD) and a group fed with powder food (PD), and sleep and physiological and anatomical changes were compared between the groups. PD exhibited less cranial bone structure development and a significant weight gain. Furthermore, these PD mice showed reduced number of neurogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Currently, modern dietary forms tend to be soft and easily digested, which dramatically influences the growth of a normal stomatognathic system (Proffit et al, 1998). Prolonged changes in masticatory function could lead to altered craniofacial morphology (Hichijo et al, 2014;Kufley et al, 2017), development of muscle fibers of masticatory muscles (Grunheid et al, 2009;Kawai et al, 2010), and neuronal connections in the hippocampus (Okihara et al, 2014;Anegawa et al, 2015). Recent studies have suggested that changes in masticatory function have an influence in motor representations within the sensorimotor cortex (Avivi-Arber et al, 2010a,b, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, modern dietary forms tend to be soft and easily digested, which dramatically influences the growth of a normal stomatognathic system (Proffit et al, 1998). Prolonged changes in masticatory function could lead to altered craniofacial morphology (Hichijo et al, 2014;Kufley et al, 2017), development of muscle fibers of masticatory muscles (Grunheid et al, 2009;Kawai et al, 2010), and neuronal connections in the hippocampus (Okihara et al, 2014;Anegawa et al, 2015). Recent studies have suggested that changes in masticatory function have an influence in motor representations within the sensorimotor cortex (Avivi-Arber et al, 2010a,b, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The number of cells stained with both Brd-U and DCX in the left hippocampal DG was counted in a blinded manner using BZ-X710® (Keyence, Osaka, Japan). Six DG regions were selected from −2.06 to +2.54 mm anteroposterior to bregma in each mouse ( 21 , 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Animal Data Relative to solid foods, soft foods seem to increase food intake, weight gain and result in adverse metabolic changes in rats, but these effects may be dependent on the type of soft-feed diet used (Anegawa et al, 2015;Desmarchelier et al, 2013;Ford, 1977;Han et al, 2018;Oka et al, 2003). Softer foods are probably preferred to harder foods because they are easier and faster to eat and digest, which may then increase preference via associative learning.…”
Section: Second Stage Of Ingestion: Food In the Mouthmentioning
confidence: 99%